DEVELOPMENT OF STATE INVESTMENT SECURITY (Economic journal of Lesya Ukrainka Volyn National University, 2024)
Abstract. The article highlights the current issues of development of investment security of the state. It was determined that today's special conditions pose challenges to strengthening the investment security of the state. Proven investment activity at the global level. The result of such activity is a real increase in investment flows from partner countries.The components of investment security are systematized: the legal environment, which is characterized by regulated regulatory and legal support, without regulatory collisions and contradictions of individual legal norms; economic and political stability; the stability of the macroeconomic environment, which includes stable inflation, low unemployment, and economic growth; developed infrastructure, which is necessary for making effective investments; geopolitical risks, which include international conflicts, sanctions, trade restrictions; innovative activity that contributes to the creation of competitive industries and attracting investments; social stability, which ensures social justice, balanced development of society, improvement of investment security.The development of scientific schools that investigate the issue of investment security is studied. The most famous scientific schools are systematized, in particular: the school of risk-oriented investment management, the school of financial security, which studies the financial aspects of the investment process, financial risks, models of financial asset valuation and financial flow management, the school of political economy, which investigates the influence of political factors on investment activity , a school of international relations, a school of normative and legal regulation, which studies the legal aspects of financial markets.It has been proven that scientific schools contribute to the development and improvement of the theory and practice of investment security through the study of various aspects of this issue from different scientific approaches.The methods, goals, forms and tools of influence on state regulation of the level of investment security are defined. It is proposed to solve priority problems for strengthening the investment security of the state. The directions of further scientific research in the field of investment security are outlined.
Keywords: investment security of the state, investment and innovation security, financial security of the state, components of investment security.